Long‐range corrected density functionals combined with local response dispersion: A promising method for weak interactions. Issue 27 (1st August 2013) - Kar, Rahul; Song, Jong‐Won; Sato, Takeshi; Hirao, Kimihiko
<x xml:space="preserve">Abstract</x> Density functional theory, in general, is considered to underestimate the weak van der Waals type of intermolecular interactions. We optimized parameters of the local response dispersion (LRD) method applied to the long‐range corrected exchange‐correlation functionals (LC‐BOP12+LRD and LCgau‐BOP+LRD) on the interaction energy for the complexes in the recently compiled S66 database and found to be comparable with the high‐level wave function‐based methods reported in Řezáč et al. (J. Chem. Theory Comput. 2011, 7, 2427). Our calculations with the S66 intermolecular complexes at equilibrium geometries suggests that the LC‐BOP12+LRD and LCgau‐BOP+LRD are well‐balanced and lower cost alternatives to the methods reported in the database. Further, test on the S66X8 database (with eight nonequilibrium points) and the HBC6 and NBC10 database shows LC+LRD method with newly optimized parameters is a promising candidate for dealing such weak interactions. Finally, the new parameterized LC+LRD method was tested on X40 benchmark halogenated complexes.Copyright © 2013 Wiley Periodicals, Inc.